Managerial decision making styles, decision making skills and organizational effectiveness amongst deans of public universities in Malaysia / Leele Susana Jamian - Jamian, Leele Susana (Institute of Graduate Studies, UiTM, 2015)
Decision making holds a fundamental function as it is pivotal in all organizations. Henceforth, quality of decision made often portray the effectiveness of leaders which subsequently affects the effectiveness of the whole organisation. In light of this, the current study aimed to explore the relationship of managerial decision making styles (DMS), decision making skills (DMSKILLS) and organizational effectiveness (OE) among deans of public universities in Malaysia. This study was guided by four research objectives and five research questions. A descriptive-correlational research design employing the mixedmethods approach was used to explore these relationships. Two groups of respondents were involved in the study namely: 54 deans and 716 subordinates from four randomly selected Malaysian public universities. Quantitative data were collected from respondents via survey while qualitative data were collected via open-ended questions and semi-structured interviews. Findings indicated that a majority of deans rated themselves as Behavioural decision-makers and this was corroborated by their subordinates…